Exploratory Analysis of the Design of Multimodal Digital Storytelling Rubrics for Strengthening Communication in the 21st Century - Aura Salsabillah Rahmatya; Rizki Hikmawan (FKIP - Universitas Riau, 2026)
Communication skills are in essential competencies 21st-century education, requiring individuals to convey ideas effectively across multiple modes. Although digital storytelling (DS) has been widely recognized as an approach to developing multimodal communication, evaluation instruments that systematically capture its narrative and multimodal complexity remain limited. This study aims to develop dimensional indicators for a multimodal digital storytelling rubric grounded in real-world digital communication practices. A qualitative-exploratory approach was employed by analyzing 100 high-engagement creators across YouTube, TikTok, and Instagram Reels. Data were analyzed using NVivo software via open coding, axial coding, and selective coding procedures. The findings reveal four key dimensions of effective digital storytelling: narrative hook, narrative structure, multimodal integration, and closing message. These dimensions highlight that successful digital communication relies on structured narratives, strategic audience engagement, and the integration of multiple semiotic modes. Based on these findings, a rubric consisting of eight indicators and four performance levels was developed to support assessment in educational contexts. This study contributes a practice-informed and empirically grounded assessment tool that bridges real-world digital practices with classroom evaluation, offering both theoretical insights into multimodal literacy and practical implications for teacher education.